A Scientometric Analysis of Highly Cited Publications and a Summary of Top 25 Articles Regarding Covid-19 - Erenler, Ali Kemal; Ay, Mehmet Oguzhan; BAYDIN, Ahmet (International Journal of Medical and Health Sciences Research, 2021)
Scientometric analyses allow to shed light to status of the current literature and provide guidance to future studies. We aimed to analyze highly cited articles in terms of study fields, authors, organizations and countries. We also summarized top 25 articles for future perspectives. The Web of Science database which allows statistical analysis of a specific subject was used for data collection. We obtained highly cited publications (cited ≥6 times) and investigated them in terms of categories, countries, authors, organizations, languages, countries and journals. We also analyzed top 25 articles from full-texts and summarized them. Majority of the highly cited articles were about General Internal Medicine. Huazhong University of Science Technology was on the top of the list followed by Harvard University. Majority of the highly cited articles were published by authors from China. Journal of Medical Virology was the leading journal followed by Science of the Total Environment. English was the most common language used in articles. Clinical characteristics, diagnostic tools and treatment methods were the popular study fields when top 25 articles were considered. Scientometric analysis of the highly cited publications revealed that China, as the origin of the pandemic, was the leading country in terms of citations. Publishers and authors should be aware of inconveniences caused by rapid publication.